2016
DOI: 10.1016/j.jana.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Development of The Johns Hopkins University School of Nursing Adult/Geriatric Primary Care Nurse Practitioner Program in HIV Prevention, Treatment, and Care

Abstract: In response to the call to create an AIDS Education and Training Center for Nurse Practitioner Education by the Health Resources and Services Administration, The Johns Hopkins University School of Nursing embarked on a transformative curriculum overhaul to integrate HIV prevention, treatment, and care into the Adult/Geriatric Nurse Practitioner Program. A six-step process outlined in the Curriculum Development for Medical Education was followed. A pilot cohort of Adult/Geriatric Nurse Practitioner students wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…We found that only one-third of PCPs in the selected Southeast locations reported any HIV-related training; the region is clearly in need of a better-prepared HIV workforce. Our results are consistent with other scientific reports showing insufficient provider competency to address the community’s HIV-related service needs [24, 25]. Although not examined in our study, PCPs’ lack of familiarity with HIV prevention tools could potentially serve as a barrier for client uptake of screening and prevention interventions [16, 26, 27].…”
Section: Discussionsupporting
confidence: 90%
“…We found that only one-third of PCPs in the selected Southeast locations reported any HIV-related training; the region is clearly in need of a better-prepared HIV workforce. Our results are consistent with other scientific reports showing insufficient provider competency to address the community’s HIV-related service needs [24, 25]. Although not examined in our study, PCPs’ lack of familiarity with HIV prevention tools could potentially serve as a barrier for client uptake of screening and prevention interventions [16, 26, 27].…”
Section: Discussionsupporting
confidence: 90%
“…A decade ago, the Institute of Medicine published its groundbreaking report: Retooling for an Aging America: Building the Health Care Workforce (2008). This report emphasized the need to increase the number of health care providers competent in providing high-quality care for the ever-growing elderly population [ 36 ]. According to previous findings, it seems possible that these results are related to America's size and economic strength [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of research conducted in the United States said that nurses who are often included in training activities are intensely proportional to their compliance in carrying out care for clients. 17 This will ultimately have an impact on clients especially in increasing their satisfaction with the nursing care that nurses have provided.…”
Section: Discussionmentioning
confidence: 99%